Experimental study on moisture-dependent energy stage evolution and damage mechanisms of siltstone under cyclic loading-unloading in brazilian splitting tests - Chen, Zhu; Yuan, Qiang; Zhang, Xiukang; Liu, Xiaoliang; Bai, Xinkuan; Chen, Yongqiang (Frontiers in Earth Science, 2025)
To investigate the tensile damage mechanism of rock mass under the coupled effects of cyclic loading and water-bearing conditions in deep engineering, this study conducts Brazilian splitting cyclic loading-unloading tests on dry and water-saturated siltstone specimens. The stress-strain characteristics, energy evolution patterns, and damage properties of rock mass under various stress path conditions are systematically analyzed. Results indicate that the plastic deformation of rock mass accumulates continuously with increasing peak stress and number of cycles, while the hysteresis loops shift toward higher strain levels. Saturated specimens exhibit a more pronounced hysteresis loop migration during initial cycles, confirming the significant influence of moisture on rock mass deformation behavior. In terms of energy evolution, both moisture content and stress path jointly govern the energy evolution mode and damage progression of rock mass. Under low to medium stress paths, energy evolution demonstrates a typical nonlinear growth pattern, with elastic energy consistently dominating. Under high stress paths, initial plastic deformation leads to a unique phenomenon where the energy curve initially decreases before rising. Moisture exerts a dual effect on energy dissipation: in the initial stage, it promotes rapid accumulation of dissipated energy through lubrication, whereas near the failure stage, the weakening effect causes instability and failure of rock mass at a lower energy threshold. The evolution stages of dissipated energy closely correspond to the characteristics of the stress-strain curves and can more sensitively reflect the internal damage evolution process of rock mass. Damage evolution analysis further reveals that saturated specimens exhibit an abrupt inflection point in damage and overlapping curve characteristics at specific stress thresholds, with their damage growth rates significantly exceeding those of dry specimens across all stress paths. The damage variable based on energy dissipation shows a strong correlation with the dissipated energy evolution stages, serving as an effective indicator for predicting rock mass damage evolution and failure.